Neuroética de la empatía: las neuronas espejo como clave de reflexión ética - Ángelo Antonio Moreno León (Azur, 2021)
This work reflects on the discovery of mirror neurons, their link with the understanding of empathy and as a key to ethical reflection. It is based on the approaches of Giacomo Rizzolatti and Corrado Sinigaglia (2006) who showed the relationship of mirror neurons with the motor system and the perception of movements as a pre-conceptual epistemological basis to understand the intentionality of others, in addition, Marco Iacoboni's (2009) proposal is analyzed, which shows the relationship of mirror neurons in the conformation of individuation and intersubjectivity, with scopes that allow an explanatory hypothesis of autism and other emerging problems such as the relationship of mirror neurons with inertial violence. Finally, biological determinism is reflected as an insufficient condition to suppress autonomy.